2020
DOI: 10.1016/j.omto.2020.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Antigen Receptor T Cell Therapy Targeting ICAM-1 in Gastric Cancer

Abstract: Cancer therapy utilizing adoptive transfer of chimeric antigen receptor (CAR) T cells has demonstrated remarkable clinical outcomes in hematologic malignancies. However, CAR T cell application to solid tumors has had limited success, partly due to the lack of tumor-specific antigens and an immune-suppressive tumor microenvironment. From the tumor tissues of gastric cancer patients, we found that intercellular adhesion molecule 1 (ICAM-1) expression is significantly associated with advanced stage and shorter su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 80 publications
2
34
2
Order By: Relevance
“…In this study, the proinflammatory mediator S100A8/A9 in combination with species-specific expression of proinflammatory cytokines IL6 (mouse) and IL8 (human) established a pro-metastatic primary tumor niche in the Hltf -deleted TME. Changes in CDX gene expression further promoted metastasis as ICAM-1 increases cancer cell invasion/intravasation into the microvasculature [ 49 ] and mediates peritoneal carcinomatosis [ 50 ] HP promotes colorectal cancer cell motility [ 51 ] and SERPINA3 promotes tumor cell migration and invasion [ 52 ]. Decreased HGF may be partly responsible for reduced liver metastasis in this model [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the proinflammatory mediator S100A8/A9 in combination with species-specific expression of proinflammatory cytokines IL6 (mouse) and IL8 (human) established a pro-metastatic primary tumor niche in the Hltf -deleted TME. Changes in CDX gene expression further promoted metastasis as ICAM-1 increases cancer cell invasion/intravasation into the microvasculature [ 49 ] and mediates peritoneal carcinomatosis [ 50 ] HP promotes colorectal cancer cell motility [ 51 ] and SERPINA3 promotes tumor cell migration and invasion [ 52 ]. Decreased HGF may be partly responsible for reduced liver metastasis in this model [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another group targeted ICAM-1 and compared intraperitoneal injection versus tail vein injection. They observed a significantly higher tumor response with intraperitoneal delivery [47].…”
Section: Car-t In Gastric Pcmentioning
confidence: 96%
“…ICAM is found more frequently in advanced stages, such as lymph-node metastases and systemic metastases [46]. In mice, the use of ICAM in CAR-T cell therapy has shown a strong capacity for tumor elimination and can also act on distant tumors [47].…”
Section: Icam (Intercellular Adhesion Molecule 1)mentioning
confidence: 99%
“…Colorectal NKG2D [54], EP-CAM [55], HER2 [56], GUCY2C [57], TAG-72 [58], CD46 [58] Liver CEA [59], Glypican3 [60], AFP [61] Gastric Mesothelin [62], ANTXR1 [63], MUC3A [63], Trop2 [64], Claudin18.2 [66], NKG2D [28], HER2 [65,66], FR-α [67] Pancreatic MUC1 [68], Mesothelin [69], αvβ6 [70], CEA [71], PSCA [71], FAP [71], CD47 [72], HER2 [73], NKG2D [74] Renal CAIX [75] Melanoma GD2 [76], GSPG4 [77], Glypican3 [78], HER2 [79] Cervix αvβ6 [80], L1-CAM [81] Neuroblastoma GD2 [82,83], CD56 [84], Glypican 2 [85], CD171 [86] Glioblastoma EGFRvIII [87], HER2 [88], B7-H3 [89], NKG2D [90], CAIX [91], αvβ3, IL13Rα2 [92] Ovarian Mesothelin [62,93], αvβ6…”
Section: Cancer Antigenmentioning
confidence: 99%
“…Based on other studies, using clau-din18.2-CAR T cells [74], NKG2D-CAR T cells [75], folate receptor 1 (FOLR1)-CAR T cells [76], and HER2-CAR T cells [77] can be considered as a novel therapeutic approach for gastric cancer therapy. In a recent study, Jung et al showed that ICAM-1 CAR T cells alone or in combination with chemotherapeutic agent paclitaxel or CAR T cells modified IL-12 release, as a promising approach which greatly improves ICAM-1 high -advanced gastric cancer patients [78].…”
Section: Gastric Cancermentioning
confidence: 99%